Comparison of different diagnostic approaches in the management of the clinically negative neck in early oral cancer patients. Issue 12 (26th February 2021) - de Bree, Remco; de Keizer, Bart
Abstract : In clinically node‐negative patients with early oral cavity cancer, [ 18 F]fludeoxyglucose (FDG) positron emission tomography–computed tomography (PET‐CT) should be compared with sentinel node biopsy. Cost effectiveness is one of the important aspects for implementation of FDG/PET‐CT in clinical practice for this patient population.